2017
DOI: 10.1115/1.4036802
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics Analyses of Porous Microchannels With Asymmetric Thick Walls and Exothermicity: An Entropic Model of Microreactors

Abstract: This paper presents a study of the thermal characteristics and entropy generation of a porous microchannel with thick walls featuring uneven thicknesses. Two sets of asymmetric boundary conditions are considered. The first includes constant temperatures at the surface of the outer walls, with the lower wall experiencing a higher temperature than the upper wall. The second case imposes a constant heat flux on the lower wall and a convection boundary condition on the upper wall. These set thermal models for micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…The temperature and Nusselt number solutions developed in Section 4 were compared with those developed by Elliott et al [15] for the case with ordinary fluid and no thermal radiation. This resulted in observing no difference between the two datasets and hence confirmed the validity of the mathematical model developed in Sections 2-4.…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature and Nusselt number solutions developed in Section 4 were compared with those developed by Elliott et al [15] for the case with ordinary fluid and no thermal radiation. This resulted in observing no difference between the two datasets and hence confirmed the validity of the mathematical model developed in Sections 2-4.…”
Section: Validationmentioning
confidence: 99%
“…For example, the small dimensions of microreactors warrants inclusion of the solid walls of microchannels within the thermophysical calculations of the system [12,13]. Further, due to the internal heat generation within the microreactor, the local thermal non-equilibrium (LTNE) approach should be applied to the thermal analyses of porous microreactors [14,15]. Owing to these complexities, thermodynamic analysis of microreactors is amongst the state-of-the-art research categories in the broad field of thermo-chemical systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As opposed to classical reaction vessels, where the vessel walls comprise a relatively small component of the total volume of the system, the walls of a microchannel are of comparable volume to that of the microchannel itself. Recent studies of microreactors have revealed the essential necessity of taking into account the enclosing structure when examining the transport of heat [18,19] and mass [17]. It is common for microreactors to feature multiple microchannels inside which chemical reactions take place [5,8].…”
Section: Introductionmentioning
confidence: 99%